A Survey Report of Nitrogen Fixing Species of Garhwal Himalaya and Some Rhizospheric Enzyme Study in Desert Soil - Chaukiyal, S. P.; Mir, Rayees Afzal (Indian Forester, 2011)
In an extensive survey to Garhwal Himalaya and arid soil of western Rajasthan. twenty four leguminous nitrogen fixing species were identified including seven herbs, nine shrubs, four climbers and four trees species which were screened for nodulation and nitrogen fixation activity between 400-2100m altitudes. Maximum and minimum nodulation and nitrogen fixation (21881.3 n molesn moles acetylene reduced pl-1 h-1) activity was recorded in Desmodium floribundum at 2000m and Atylosia scarabaeoides (56.4 n moles) at 900m altitude respectively. In desert ecosystem, five herbs, two shrubs and three climbers were tested for rhizophoric soil acid and alkaline phosphate and dehydrogenase activity. Minimum and maximum acid phosphatase activity was recorded in Rhynchosia minima and Indigofera argentea and alkaline phosphatase in Indigofera linnaei Ali, and Indigofera sessiliflora. Whereas, minimum and maximum dehydrogenase activity was observed in Alysicarpus longifolius and Indigofera sessiliflora respectively. The identified herb, shrub and climber species may be useful for conservation of degraded site under harsh climatic conditions in temperate Himalayan and Rajasthan desert ecosystem.